Cannabidiol's cytotoxicity in pancreatic cancer is induced via an upregulation of ceramide synthase 1 and ER stress - Nagina Mangal; Vikash Reebye; Nagy Habib; Mikael H. Sodergren (BMC, 2024)
Abstract Pancreatic ductal adenocarcinoma (PDAC) remains one of the most aggressive malignancies with a median 5 year-survival rate of 12%. Cannabidiol (CBD) has been found to exhibit antineoplastic potential and may potentiate the anticancer effects of cytotoxic's such as gemcitabine. CBD therapy has been linked to de novo synthesis of ceramide. The sphingolipid ceramide is a potent tumour suppressor lipid with roles in apoptosis and autophagy. One of the key players involved is ceramide synthase, an enzyme with six isoforms (CerS1-CerS6), reported to have disease prognostic value. Quantitative real time PCR was used to determine mRNA expression levels of ceramide synthase isoforms, GRP78, ATF4 and CHOP. Western blotting was used to analyze protein expression of these markers and knockdown of CerS1 and GRP78 were applied via an siRNA and confirmed by the two mentioned methods. Mice with PDAC xenografts were injected via intraperitoneal method with drugs and tumours were analysed with flow cytometry and processed using H&E and IHC staining. siRNA knockdown of ceramide synthase 1 (CerS1) and analysis point to evidence of a putative CerS1 dependent pathway driven by CBD in activating endoplasmic reticulum (ER) stress target; GRP78. Upon CBD treatment, CerS1 was upregulated and downstream this led to the GRP78/ATF4/CHOP arm of the unfolded protein response (UPR) pathway being activated. In an in vivo model of PDAC in which CerS1 was not upregulated on IHC, there was no observed improvement in survival of animals, however a reduction in tumour growth was observed in combination chemotherapy and CBD group, indicating further investigations in vivo. These findings provide evidence of a potential ceramide induced cytotoxic mechanism of action of CBD in pancreatic ductal adenocarcinoma.